2017
DOI: 10.1111/ggi.13134
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of home‐based exercise in older patients with advanced chronic obstructive pulmonary disease: A 3‐year cohort study

Abstract: Aim: To determine whether home-based exercise can improve clinical outcomes in older patients with advanced chronic obstructive pulmonary disease using long-term oxygen therapy.Methods: Information was provided to improve chronic obstructive pulmonary disease self-management before the onset of the present prospective 3-year cohort study. Patients selected either home-based exercise using a lower-limb cycle machine (ergo-bicycle; group E), or usual exercise (group U). To assess self-management, the Lung Inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…There exists evidence regarding the efficacy of domiciliary exercise-based treatments in patients with respiratory disorders. Based on this, it could become the therapeutic method of choice to allow the treatment and supervision of isolated patients due to infection during home confinement [15][16][17]. It has been suggested that a session of exercise through a telerehabilitation system may be a feasible option to manage quarantined patients with COVID-19 [18,19], enabling physiotherapists to provide interactive treatments by means of different devices [20].…”
Section: Introductionmentioning
confidence: 99%
“…There exists evidence regarding the efficacy of domiciliary exercise-based treatments in patients with respiratory disorders. Based on this, it could become the therapeutic method of choice to allow the treatment and supervision of isolated patients due to infection during home confinement [15][16][17]. It has been suggested that a session of exercise through a telerehabilitation system may be a feasible option to manage quarantined patients with COVID-19 [18,19], enabling physiotherapists to provide interactive treatments by means of different devices [20].…”
Section: Introductionmentioning
confidence: 99%
“…Long COVID can be a range of symptoms that typically last awhile after an individual is initially More often than not, respiratory issues are treated by physical therapy in a hospital setting, but home based health care is an option that allows patients the comfort level of their own homes when recovering from any type of illness or disorder. The treatment program for these patients will consist of therapeutic exercises that target respiration through breathing training 2,19,20,21 .…”
Section: Long Covid or Post Covid Syndromementioning
confidence: 99%
“…Patients with COPD who self-selected to purchase a lower limb cycle machine and participate in tailored self-management education experienced similar decline in dyspnea measured by the Modified Medical Research Council as that in patients in the usual exercise control group. 52 Patients in the intervention group were encouraged to use the cycle machine for at least 20 minutes per day with intensity measured by dyspnea between 3 and 4 on the modified Borg scale. No measure of exercise adherence was reported.…”
Section: Home-based Exercisementioning
confidence: 99%